Microscopic defects as the limiting factor in the direct transmission of nanocoatings obtained through self‐assembly - Loïc O. Le Cunff; Hind Kadiri; Gilles Lérondel (Nano Select, 2021)
Abstract Colloidal lithography is a very popular method to achieve large‐scale antireflective coatings. Those sometimes display large a falloff in direct transmission for short wavelengths, which has been linked to scattering. This work proposes, through finite‐difference time‐domain calculations of “supercells,” an explanation of those scattering losses by simulating crystalline defects much larger than the individual microstructures. The results are in agreement with the experimental data, suggesting those defects are indeed the driving force behind this scattering.